The Effect of Empowering Leadership and Adversity Quotient on Teacher’s Performance - Jasti Karyani; Dessy Wardiah; Andi Rahman (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to examine the individual and simultaneous influence of empowering leadership and adversity quotient (AQ) on the performance of kindergarten teachers. Employing a quantitative survey method with a correlational approach, data were collected via questionnaires from 58 teachers in Ilir Barat I District, Palembang City, and analyzed using correlation and multiple regression. The results confirm significant positive influences: empowering leadership alone explains 43.9% of performance variance (r=0.664), while AQ alone explains 58.6% (r=0.766). Simultaneously, both variables account for 59.3% of performance variance (r=0.770), with the regression equation Ŷ = 36.606 + 0.15X1 + 0.585X2. The novelty lies in empirically testing this specific variable combination within early childhood education, a less explored context. A key practical implication is the need for integrated professional development programs that combine leadership empowerment with resilience training to optimize teacher efficacy. This study contributes concrete empirical data and a predictive model to the educational management literature, highlighting the substantial role of psychological resilience alongside leadership in enhancing teacher’s performance.